Analyzing the Dynamics of School Dropout in Upper Secondary Education in Latin America : A Cohort Approach - Bentaouet Kattan, Raja; Székely, Miguel (World Bank Group, Washington, DC, 2015)
This study examines trends in school dropout at the upper secondary education level across Latin America over the past two decades, and attempts to identify factors influencing these rates. The methodology contributes to the existing literature by employing repeated cross sections of data to track the life cycle path of representative groups of individuals belonging to a birth cohort, by constructing and analyzing a synthetic data base of household survey data from 18 countries. A key finding is that while upper secondary enrollment rates increased in the region, the proportion of upper secondary age youth dropping out of school has remained persistently high, despite relatively favorable macroeconomic conditions. Furthermore, the study traces the moment in the life cycle at which the majority of dropout takes place to reveal differences between countries. Finally, to explain the trends in upper secondary dropout rates, the study examines the impact of three groups of factors: (i) shifts in the cohort size and socioeconomic composition of the population eligible for entering upper secondary education; (b) the macroeconomic environment and labor market opportunities; and (c) the returns to schooling. A series of regressions shows that an important factor that may be driving higher dropout levels has been the higher numbers of students from poor socioeconomic backgrounds reaching the upper secondary level. In addition, high returns to education have been a pull factor into the schooling system, while, especially in countries where the majority of youth dropout early (prior to upper secondary education), the data confirm an apparent substitution effect due to the opportunity cost of forgoing employment opportunities. Overall, the findings confirm the importance of policy makers' focus on upper secondary education across Latin America and suggest implications for focusing the policy agenda.